Molecular Docking and ADMET Prediction Studies of Flavonoids as Multi-target Agents in COVID-19 Therapy: Anti-inflammatory and Antiviral Approaches - Arief Adi Nugroho; Muhammad Sulhan Hadi; Candra Adianto; Juniawan Akbar Kharisma Putra; Hari Purnomo; Nanang Fakhrudin (Indonesian Journal of Pharmacy, 2023)
Recent studies showed that hyper-inflammatory reactions including cytokines storm leads to acute respiratory distress syndrome and responsible for death toll in COVID-19. Thus, the pathways involved in inflammation and SARS-Cov-2 replication represent a promising therapeutic target. By employing a computational model, we investigated the effect of plant flavonoids on pro-inflammatory proteins (glucocorticoid receptor (GR), cyclooxygenase-2 (COX-2) and 5-lipoxygenase (LOX) enzymes), and on proteins involved in virus replication (main protease (Mpro), and papain-like protease (PLpro)). This in silico study study aimed to identify promising flavonoids with anti-inflammatory and antiviral activities (multi-target) for combating COVID-19. Mpro (PDBID: 6LU7), PLpro (PDBID: 6WX4), COX-2 (PDBID: 6COX), LOX (PDBID: 6N2W), and GR (PDBID: 1P93) were selected as target proteins. The molecular docking experiment was done using PLANTS software. Parameters for Lipinski’s “Rule-of-Five'', and the prediction of pharmacokinetic and toxicity profiles were done using the online platform, pkCSM. We found that 2 flavonoids, diosmin and hesperidin demonstrated low binding score and stronger than that of the reference ligands for the target proteins of Mpro, PLpro, and LOX. These compounds interact with amino acid residues of the protein targets through hydrogen bonds and show similar binding pattern compared to the approved drugs and native ligands. The ADMET and drug-likeness profiles prediction indicated that they have low toxicity, and good pharmacokinetic properties with the exception of the absorption profile. Hesperidin and diosmin are the promising candidates to be further investigated as multi-target agent for the treatment of COVID-19 through simultaneous inhibition of inflammation and virus replication.